Peran Sastra dalam Membangun Karakter Mahasiswa pada Sebuah Pendekatan Pendidikan - Anita Candra Dewi; Usman, Usman; Asrifan, Andi (AIJER: Algazali International Journal Of Educational Research, 2024)
This article discusses the role of literature in shaping students' character through a holistic educational approach. Literature is understood from two perspectives: as a science that teaches critical analysis of moral and social values, and as an art that emphasizes aesthetic experience and the development of empathy. In addition, literary genres such as poetry, prose, and drama enrich students' understanding of the diversity of human expression. Literary movements such as romanticism, realism, naturalism, and modernism show how socio-cultural changes affect literary works. Through this understanding, students are invited to think critically, develop moral sensitivity, and build social awareness, so that literature becomes an important instrument in character education.